Latinos' Perceptions of Intergroup Relations in the United States: The Cultivation of Group‐Based Attitudes and Beliefs from English‐ and Spanish‐Language Television. (March 2015) - Ortiz, Michelle; Behm‐Morawitz, Elizabeth; Mastro, Dana; Tukachinsky, Riva
<x xml:space="preserve">Abstract</x> This study utilized a social identity‐based cultivation approach to investigate the influence of English and Spanish‐language television exposure in the United States on Latinos' perceptions of intergroup relations. Although research has examined the influence of television on Whites' perceptions of nondominant racial and ethnic groups, little empirical research exists assessing the influence of television on nondominant group members' (e.g., Latinos') race‐related perceptions. To help fill this gap, a survey of Latino Americans (N = 209) was conducted. Results indicated that Latinos' English‐language television exposure was associated with perceptions of discrimination against Latinos and perceptions of the legitimacy of such treatment. Endorsement of English‐language television portrayals and exposure to Spanish‐language television moderated these relationships.